An Overview of Parental Alienation on Child Custody and Ḥadanah Cases - Sarah Sakinah Azman; Asmidah Ahmad (Faculty of Syariah and Law, USIM, 2026)
Parental alienation (PA) can be defined as a mental condition involving the rejection from a child towards one parent under custody matter. Parental alienation has been discussed widely by international scholars however this matter seems less known in Malaysian society. The purpose of this study is to understand the extent of discussion regarding parental alienation on determining the right of custody in court in Malaysia and to identify whether it is a crime along with-it consequences on children involved. Various discussions on parental alienation have led to different opinions and views. Some argued that parental alienation is one of the forms of child abuse reasoning the act tends to be committed by a party who wants to dominate his right using the child to oppose another party. Nonetheless, in Malaysia, this issue has not been discussed in detail hence this study mostly manages to refer to writings from the United States and other countries. The methodology used is qualitative where it focuses on library-based research and related provisions from statues, cases regarding child custody from both civil court and Syariah court and selected materials from books, journals, articles. The findings indicate parental alienation is not an offence in Malaysia and there is no specific law regarding parental alienation. Although parental alienation cannot be considered as a crime, the court has recognized the existence of it and one party can take a legal action against another party under civil litigation separately. Therefore, through this writing, it is hoped to provide an enlightenment on the issue of parental alienation in child custody and ḥaḍānah cases.